Kelengkapan Sarana Prasarana Pada Kelompok Bermain Menuju Lingkungan Ramah Anak - Hasanah, Uswatun; Fauzia, Wulan; Kaswati, Angggar; Rahayu, Supriati Hardi; Zilfa, Rohil (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2024)
Exploring the implementation of an early childhood friendly school environment at the al-Husan KB is the main priority in this research. This research uses descriptive qualitative methods by means of observation, interviews, documentation, and data triangulation as data collection techniques. The results are: 1) Al-Husna's child-friendly environment is able to provide facilities and infrastructure that can meet the needs of children to grow and develop without any obstacles, feeling safe and comfortable. A child-friendly environment is a place that can support children's rights being fulfilled without any obstacles or threats. The inhibiting factor for its implementation is that parental intervention, which is allowed to wait in the school environment, means that children often have difficulty moving around to play at the yard.